Integration of Banking Law Competencies and Fraud Law Enforcement in the Development of the Law Study Program - Grace Henni Tampongangoy; Lendy Siar; Meylan Maasye Maramis (Transpublika Publisher, 2026)
The development of the banking industry and the increasing complexity of financial crimes have created new challenges for legal education institutions in preparing graduates who are competent and adaptive to labor market needs. This article aims to analyze the importance of integrating banking law competencies and fraud law enforcement in the development of the Law Study Program. This study uses a normative juridical method with statutory, conceptual, and analytical approaches supported by literature studies and recent academic literature and official regulatory documents. The results show that criminal acts of fraud in the banking sector, particularly those involving directors and internal banking actors, require legal professionals with comprehensive understanding of banking regulations, corporate governance, compliance systems, financial crime investigation, and law enforcement mechanisms. Therefore, legal education institutions are required to reformulate their curricula to align with the dynamics of the banking sector and the digital financial ecosystem. The integration of banking law competencies and fraud law enforcement can be carried out through curriculum strengthening, case-based learning, professional certification, internship programs at banking institutions, and cooperation with financial sector regulatory authorities. This integration is expected to improve graduate competitiveness, strengthen professional legal competencies, and contribute to the prevention and enforcement of law against banking crimes in Indonesia.